Neurectomy in Mesh Repair of Inguinal Hernia; to Reduce Inguinodynia - Mulkipatil, S. Y.; Kuntoji, S. B. (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Introduction: Incidence of long term (\(\ge\)1 year) post operative neuralgia reported for Lichtenstein repair of inguinal hernia range from 6 – 29 %. Routine ilioinguinal nerve excision has been proposed as a means to avoid the troubling complication of long-+++term post herniorrhaphy neuralgia. Theoretically, excision of ilioinguinal nerve would eliminate the possibility of inflammation neuralgia arising from entrapment, neuroma, fibrotic reactions, yet controversies persists and the procedure is not widely accepted. Materials and Methods: Total100 patients, diagnosed as inguinal hernia and admitted in Tertiary care hospital in North Karnataka and candidates for elective open mesh repair were enrolled and divided into 2 groups, Group A, nerve is preserved, Group B, neurectomy. All patients underwent same type of surgery, Lichtenstein Tension Free Mesh Repair. Post operative follow up was done personally on day 1, day 3, day 7, at 1 month. Whereas at 3 months and at 6 months, follow up done personally and telephonically. Results: The incidence of post operative groin pain was compared in Ilioinguinal nerve preservation versus routine excision of ilioinguinal nerve. It was found that incidence of severe pain was 36% vs. 6% at POD-1, Moderate pain 94% vs. 22% at POD-3, Moderate pain 78% vs. 10% at POD-7 and No pain 8% vs. 35% after 1 month of surgery respectively in the two groups. Whereas, there was no pain in 32% vs. 96% after 3 months of surgery and no pain in 68% vs. 76% after 6 months (16 patients missed the follow up) of surgery respectively. The incidence of post operative hyperaesthesia at groin in ilioinguinal nerve preservation group was 10%, 14%, and 6% at POD-1, POD- 3 and POD-7 respectively. Whereas no hyperesthesia seen after 1 month, 3 months and 6 months. Hyperesthesia was not at all observed in neurectomy group. Incidence of post operative hypoesthesia and numbness at groin between the two groups at all post-operative follow up was found to be non significant Conclusion: The present prospective comparative study revealed decreased incidence of chronic groin pain after surgery in neurectomy group. Furthermore, the procedure is not significantly associated with additional morbidities like Hyperaesthesia, Hypoesthesia and numbness.